Densidad de la madera de Eucalyptus grandis a los 11 años de edad según densidad de plantación en Misiones, Argentina = Wood density of Eucalyptus grandis at 11 years of age according to planting density in Misiones, Argentina - Keller, Aldo Esteban; Barth, Sara Regina; Aquino, Diego Rolando; Feldmann, Alexis (Facultad de Ciencias Forestales, Universidad Nacional de Misiones (UNaM) y EEA Montecarlo, INTA, 2024)
This work aims to analyze the effect of planting density on wood density, from an experiment of different planting densities of Eucalyptus grandis, with 4 treatments. Density treatments were defined as 2,500, 1,250, 625, and 312 trees per hectare. No significant differences in wood density were observed due to different planting densities. On the other hand, a notable trend could be observed in the axial variation of the wood density, being greater at a greater distance from the pith.